The spectrum of Notch3 mutations in 28 Italian CADASIL families. Issue 5 (15th April 2005) - Dotti, M T; Federico, A; Mazzei, R; Bianchi, S; Scali, O; Conforti, F L; Sprovieri, T; Guidetti, D; Aguglia, U; Consoli, D; Pantoni, L; Sarti, C; et al.
Abstract : Background: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) is a cause of hereditary cerebrovascular disease. It results from mutations in the Notch3 gene, a large gene with 33 exons. A cluster of mutations around exons 3 and 4 was originally reported and limited scanning of these exons was suggested for the diagnosis in most cases. Objective: To report Notch3 mutation analysis in 28 unrelated Italian CADASIL families from central and south Italy. Results: The highest rate of mutations was found in exon 11 (21%) and only 18% of mutations were in exon 4. This may be related to the peculiar distribution of Notch3 mutations in the regions of origin of the families. Conclusions: The results suggest that limited scanning of exons 3 and 4 is inadvisable in CADASIL cases of Italian origin.